Soil Temperature and Nutrient Availability - Hunsigi, Gururaj (Annals of Arid Zone, 2016)
1. Nutrient availability is governed chiefly by three processes viz., diffusion, mass flow and root interception Mhich largely affected by soil temperature. 2. Ions like Ca++, Mg++ and NO3-are made available by mass flow while NH4,+’ Rb++, Zn++, Mn++, Fe++ and P are made available by diffusion. 3. Soil temperature affects the root extension and the "effective soil volume" is reduced at low temperature which might also diminish the effectiveness of root as "sink". The net result is the reduced nutrient availability. It is concluded that the effects of soil temperature on nutrient availability is not known under Indian conditions. It is likely that the yearly variation in crop response to applied fertilizers may be partly ascribable to variation in soil temperature. Cold temperature encountered in winter may reduce the nutrient availability. Mulching with st,raw, spreading translucent plastic films help to warm the soil. Ridges and orientation of plants in North-South rows may increase soil temperature favourably. Electrical methods of soil heating will be too expensive. However, in "summer very high temperatures attained may fix the added P. Shading ’and irrigation is a common agronomic practice to lower the soil temperatures favourably.